Future of Malaysian youths at risk: mental health, self-efficacy, and behavioural change - Adnan, Wardatul Hayat; Abdul Aziz, Ahlam; Mohamed, Shazleen; Sahharon, Hamizah; Mohamed, Shafizan (University of Malaya, 2024)
High rates of mental health problems have become a growing concern in Malaysia’s higher education, negatively impacting students’ behaviour. Despite the serious nature of poor mental health, students often do not seek help because of negative behavioural changes. Identifying the youth’s past behaviour, demographic culture, personality, moods & emotions, and media intervention can further determine the youths’ level of mental health as early detection is vital in reducing the risk of mental health issues amongst them. Recent mental health research reports that self-efficacy is associated with better mental health and decreased negative behavioural change. However, relationships between those constructs remain to be evaluated among youths in Malaysia. This study aims to appraise the connections between mental health problems, self-efficacy, and behavioural change in this population. An opportunity sample of 201 students from a public university completed questionnaires regarding these constructs. Correlation, regression, and path analyses were conducted. Mental health problems were found to be positively associated with self-efficacy and behavioural change. The findings suggest that self-efficacy is essential for the mental health of Malaysian youths and is associated with negative ehaviour. In order to prevent teenage mental health issues and low self-efficacy, education and awareness are crucial. Since many people might not fully comprehend these ideas, education is the first line of action.